Short-Range Market Reaction to Changes to LIFO Accounting Using Preliminary Earnings Announcement Dates - Brown, Robert Moren (Journal of Accounting Research, 1980)
Numerous empirical studies (Archibald [1972], Ball [1972], Sunder [1973], and Comiskey [1971], to mention a few) have demonstrated market efficiency with respect to accounting information. In general, these studies have shown that the market is not fooled by accounting changes which manipulate reported income. Despite these research findings, the that stock prices move in the direction of an accounting change's impact on reported income persists. This view is illustrated by the following statement, which appeared in the Wall Street Journal (October 7, 1974): Because of the negative impact on earnings LIFO conversions haven't always been welcome news to the stock market ... also companies worried about a takeover may be reluctant to risk the kind of downward pressure on stock prices that has greeted other companies when they recently converted to LIFO. Is the traditional merely incorrect, or does it have some demonstrable basis? Most of the previous research designed to analyze market reaction to accounting changes has employed a methodology which would tend to show long-range effects. This implies that support for the traditional view, if it exists, might come from observing short-range market reaction to accounting changes. Kaplan and Roll [1972] employed a shortrange methodology to study market reaction to changes in the treatment of the investment tax credit and changes in depreciation method. While they stated that they had difficulty discerning any statistically signifi-